Presentation is loading. Please wait.

Presentation is loading. Please wait.

8. DERIVATIVES OF INVERSE TRIG FUNCTIONS

Similar presentations


Presentation on theme: "8. DERIVATIVES OF INVERSE TRIG FUNCTIONS"โ€” Presentation transcript:

1 8. DERIVATIVES OF INVERSE TRIG FUNCTIONS
๐‘ฆ= arc ๐‘ ๐‘–๐‘› ๐‘ฅ ๐‘ฆ= ๐‘ ๐‘–๐‘› โˆ’1 ๐‘ฅ ๐‘ฆ= arc ๐‘๐‘œ๐‘  ๐‘ฅ ๐‘ฆ= ๐‘๐‘œ๐‘  โˆ’1 ๐‘ฅ sin ๐‘ฆ =๐‘ฅ cos ๐‘ฆ =๐‘ฅ ๐‘‘ ๐‘‘๐‘ฅ sin ๐‘ฆ = ๐‘‘ ๐‘‘๐‘ฅ ๐‘ฅ ๐‘‘ ๐‘‘๐‘ฅ cos ๐‘ฆ = ๐‘‘ ๐‘‘๐‘ฅ ๐‘ฅ cos ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ =1 โˆ’ sin ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ =1 ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ = 1 cos ๐‘ฆ = โˆ’ ๐‘ ๐‘–๐‘› 2 ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ = 1 โˆ’๐‘ ๐‘–๐‘› ๐‘ฆ =โˆ’ 1 1โˆ’ ๐‘๐‘œ๐‘  2 ๐‘ฆ ๐‘‘ ๐‘‘๐‘ฅ ๐‘Ž๐‘Ÿ๐‘ sin ๐‘ฅ = 1 1โˆ’ ๐‘ฅ 2 ๐‘‘ ๐‘‘๐‘ฅ ๐‘Ž๐‘Ÿ๐‘ cos ๐‘ฅ =โˆ’ 1 1โˆ’ ๐‘ฅ 2

2 ๐‘ฆ= arc ๐‘ก๐‘Ž๐‘› ๐‘ฅ ๐‘ฆ= ๐‘ก๐‘Ž๐‘› โˆ’1 ๐‘ฅ ๐‘ฆ= arc ๐‘๐‘œ๐‘ก ๐‘ฅ ๐‘ฆ= ๐‘๐‘œ๐‘ก โˆ’1 ๐‘ฅ ๐‘ก๐‘Ž๐‘› ๐‘ฆ =๐‘ฅ ๐‘๐‘œ๐‘ก ๐‘ฆ =๐‘ฅ ๐‘‘ ๐‘‘๐‘ฅ ๐‘ก๐‘Ž๐‘› ๐‘ฆ = ๐‘‘ ๐‘‘๐‘ฅ ๐‘ฅ ๐‘‘ ๐‘‘๐‘ฅ co๐‘ก ๐‘ฆ = ๐‘‘ ๐‘‘๐‘ฅ ๐‘ฅ ๐‘๐‘œ๐‘  2 ๐‘ฆ+ ๐‘ ๐‘–๐‘› 2 ๐‘ฆ ๐‘๐‘œ๐‘  2 ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ =1 โˆ’๐‘ ๐‘–๐‘› 2 ๐‘ฆ โˆ’๐‘๐‘œ๐‘  2 ๐‘ฆ ๐‘ ๐‘–๐‘› 2 ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ =1 1 ๐‘๐‘œ๐‘  2 ๐‘ฆ 1 ๐‘๐‘œ๐‘  2 ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ = ๐‘๐‘œ๐‘  2 ๐‘ฆ ๐‘ ๐‘–๐‘› 2 ๐‘ฆ+๐‘๐‘œ๐‘  2 ๐‘ฆ 1 ๐‘ ๐‘–๐‘› 2 ๐‘ฆ 1 ๐‘ ๐‘–๐‘› 2 ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ =โˆ’ ๐‘ ๐‘–๐‘› 2 ๐‘ฆ ๐‘ ๐‘–๐‘› 2 ๐‘ฆ+๐‘๐‘œ๐‘  2 ๐‘ฆ ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ = 1 ๐‘ก๐‘Ž๐‘› 2 ๐‘ฆ+1 ๐‘‘๐‘ฆ ๐‘‘๐‘ฅ =โˆ’ 1 1+ ๐‘๐‘œ๐‘ก 2 ๐‘ฆ ๐‘‘ ๐‘‘๐‘ฅ ๐‘Ž๐‘Ÿ๐‘ tan ๐‘ฅ = 1 1+ ๐‘ฅ 2 ๐‘‘ ๐‘‘๐‘ฅ ๐‘Ž๐‘Ÿ๐‘ cot ๐‘ฅ =โˆ’ 1 1+ ๐‘ฅ 2

3 To get derivatives of inverse trigonometric functions we were able to use implicit differentiation.
Sometimes it is not possible/plausible to explicitly find inverse function, but we still want to find derivative of inverse function at certain point (slope). QUESTION: What is the relationship between derivatives of a function and its inverse ????

4 DERIVATIVE OF THE INVERSE FUNCTIONS
example: Let ๐‘“ and ๐‘” be functions that are differentiable everywhere. If ๐‘” is the inverse of ๐‘“ and if ๐‘”(โˆ’2) = 5 and ๐‘“ โ€ฒ(5) = โˆ’1/2, what is ๐‘”โ€ฒ(โˆ’2)? Since ๐‘” is the inverse of ๐‘“ you know that ๐‘“(๐‘”(๐‘ฅ)) = ๐‘ฅ holds for all ๐‘ฅ. Differentiating both sides with respect to ๐‘ฅ, and using the the chain rule: ๐‘“โ€ฒ ๐‘”(๐‘ฅ) ๐‘”โ€ฒ(๐‘ฅ) = 1 ๐‘‘๐‘“ ๐‘‘๐‘” ๐‘‘๐‘” ๐‘‘๐‘ฅ =1 So ๐‘“โ€ฒ ๐‘” โˆ’2 ๐‘”โ€ฒ(โˆ’2) = 1 โ‡’ โˆ’ ๐‘” โ€ฒ โˆ’2 =1 โ‡’ ๐‘“ โ€ฒ 5 ๐‘” โ€ฒ โˆ’2 =1 ๐‘” โ€ฒ โˆ’2 =โˆ’2

5 But not you. ๐‘“(๐‘”(๐‘ฅ)) = ๐‘ฅ The relation
๐‘” โ€ฒ ๐‘ฅ = 1 ๐‘“โ€ฒ(๐‘” ๐‘ฅ ) ๐‘“ โˆ’1 โ€ฒ ๐‘ฅ = 1 ๐‘“โ€ฒ( ๐‘“ โˆ’1 ๐‘ฅ ) used here holds whenever ๐‘“ and ๐‘” are inverse functions. Some people memorize it. But not you. It is easier to re-derive it any time you want to use it, by differentiating both sides of ๐‘“(๐‘”(๐‘ฅ)) = ๐‘ฅ (which you should know in the middle of the night).

6 A typical problem using this formula might look like this:
example: A typical problem using this formula might look like this: Given: Find: ๐‘“ 3 =5 โ‡’ ๐‘” 5 =3 ๐‘“โ€ฒ ๐‘”(๐‘ฅ) ๐‘”โ€ฒ(๐‘ฅ) = 1 ๐‘“(๐‘”(๐‘ฅ)) = ๐‘ฅ ๐‘“โ€ฒ ๐‘”(5) ๐‘”โ€ฒ(5) = 1. ๐‘“โ€ฒ(3)๐‘”โ€ฒ(5) = 1.

7 example: If ๐‘“(๐‘ฅ)=2๐‘ฅ+cosโก๐‘ฅ, find ( ๐‘“ โˆ’1 )โ€™(1) ๐‘“ 0 =1 โ‡’ ๐‘” 1 =0 ๐‘” โ€ฒ 1 = 1 ๐‘“โ€ฒ(0) = 1 2โˆ’ sin 0 ๐‘” โ€ฒ 1 = 1 2 ๐‘“โ€ฒ ๐‘”(๐‘ฅ) ๐‘”โ€ฒ(๐‘ฅ) = 1 ๐‘“(๐‘”(๐‘ฅ)) = ๐‘ฅ ๐‘“โ€ฒ ๐‘”(1) ๐‘”โ€ฒ(1) = 1 ๐‘“โ€ฒ ๐‘”(1) ๐‘”โ€ฒ(1) = 1

8 Graphical Interpretation
If ๐‘“(๐‘) = ๐‘Ž, then f -1(a) = b. (f -1)โ€™(a) = tan ๏ฆ. fโ€™(b) = tan ๏ฑ ๏ฑ + ๏ฆ = ฯ€/2 ๐‘“ โˆ’1 โ€ฒ =tan ๏ฆ= tan ๐œ‹ 2 โˆ’๐œƒ =cot ๐œƒ= 1 tan ๐œƒ = 1 ๐‘“โ€ฒ(๐‘) ๐‘“ โˆ’1 โ€ฒ (๐‘Ž)= 1 ๐‘“โ€ฒ ๐‘“ โˆ’1 (๐‘Ž) ๐‘“ โˆ’1 โ€ฒ (๐‘ฅ)= 1 ๐‘“โ€ฒ ๐‘“ โˆ’1 (๐‘ฅ) ๐‘ก๐‘Ÿ๐‘ข๐‘’ โˆ€ ๐‘Ž, ๐‘ ๐‘œ: Derivative of the inverse function at a point is the reciprocal of the derivative of the function at the corresponding point. Slope of the line tangent to ๐’‡ โˆ’๐Ÿ at ๐’™=๐’ƒ is the reciprocal of the slope of ๐’‡ at ๐’™=๐’‚.

9 example: ๐‘“ ๐‘ฅ =2 ๐‘ฅ 5 + ๐‘ฅ 3 +1 Find: ๐‘Ž ๐‘“ 1 ๐‘Ž๐‘›๐‘‘ ๐‘“โ€ฒ(1)
๐‘Ž ๐‘“ 1 ๐‘Ž๐‘›๐‘‘ ๐‘“โ€ฒ(1) ๐‘ ๐‘“ โˆ’ ๐‘Ž๐‘›๐‘‘ ๐‘“ โˆ’1 โ€ฒ 4 ๐‘“ โ€ฒ ๐‘ฅ =10 ๐‘ฅ 4 +3 ๐‘ฅ 2 ๐‘–๐‘  ๐‘๐‘œ๐‘ ๐‘–๐‘ก๐‘–๐‘ฃ๐‘’ ๐‘’๐‘ฃ๐‘’๐‘Ÿ๐‘ฆ๐‘คโ„Ž๐‘’๐‘Ÿ๐‘’ โ†’ ๐‘“ ๐‘ฅ ๐‘–๐‘  ๐‘ ๐‘ก๐‘Ÿ๐‘–๐‘๐‘ก๐‘™๐‘ฆ ๐‘–๐‘›๐‘๐‘Ÿ๐‘’๐‘Ž๐‘ ๐‘–๐‘›๐‘” โ†’ ๐‘“ ๐‘ฅ โ„Ž๐‘Ž๐‘  ๐‘Ž๐‘› ๐‘–๐‘›๐‘ฃ๐‘’๐‘Ÿ๐‘ ๐‘’ ๐‘“ 1 =4 ๐‘“ โ€ฒ 1 =13 ๐‘ƒ๐‘œ๐‘–๐‘›๐‘ก 1,4 ๐‘–๐‘  ๐‘œ๐‘› ๐‘กโ„Ž๐‘’ ๐‘๐‘ข๐‘Ÿ๐‘ฃ๐‘’ ๐‘“ ๐‘ฅ =2 ๐‘ฅ 5 + ๐‘ฅ 3 +1 โ†’๐‘ƒ๐‘œ๐‘–๐‘›๐‘ก 4,1 ๐‘–๐‘  ๐‘œ๐‘› ๐‘กโ„Ž๐‘’ ๐‘๐‘ข๐‘Ÿ๐‘ฃ๐‘’ ๐‘“ โˆ’1 ๐‘ฅ โ†’ ๐‘“ โˆ’1 4 =1 ๐‘“ ๐‘“ โˆ’1 ๐‘ฅ = ๐‘ฅ ๐‘“โ€ฒ ๐‘“ โˆ’1 ๐‘ฅ ๐‘“ โˆ’1 โ€ฒ ๐‘ฅ =1 ๐‘“โ€ฒ ๐‘“ โˆ’ ๐‘“ โˆ’1 โ€ฒ 4 =1 ๐‘“ โˆ’1 โ€ฒ (4)= 1 ๐‘“โ€ฒ 1 = 1 13 ๐‘“โ€ฒ 1 ๐‘“ โˆ’1 โ€ฒ 4 =1

10 Since ๐‘“(๐‘ฅ) is strictly increasing near ๐‘ฅ = 8, ๐‘“ โ€ฒ ๐‘ฅ =15 ๐‘ฅ 2 +1
example: ๐‘“ ๐‘ฅ =5 ๐‘ฅ 3 +๐‘ฅ+8 Find: ๐‘“ โˆ’1 โ€ฒ 8 Since ๐‘“(๐‘ฅ) is strictly increasing near ๐‘ฅ = 8, ๐‘“ โ€ฒ ๐‘ฅ =15 ๐‘ฅ 2 +1 ๐‘“(๐‘ฅ) has an inverse near ๐‘ฅ =8. ๐‘“ 0 =8 ๐‘ƒ๐‘œ๐‘–๐‘›๐‘ก 0,8 ๐‘–๐‘  ๐‘œ๐‘› ๐‘กโ„Ž๐‘’ ๐‘๐‘ข๐‘Ÿ๐‘ฃ๐‘’๐‘“ ๐‘ฅ =5 ๐‘ฅ 3 +๐‘ฅ+8 โ†’๐‘ƒ๐‘œ๐‘–๐‘›๐‘ก 8,0 ๐‘–๐‘  ๐‘œ๐‘› ๐‘กโ„Ž๐‘’ ๐‘๐‘ข๐‘Ÿ๐‘ฃ๐‘’ ๐‘“ โˆ’1 ๐‘ฅ ๐‘“ ๐‘“ โˆ’1 ๐‘ฅ = ๐‘ฅ ๐‘“โ€ฒ ๐‘“ โˆ’ ๐‘“ โˆ’1 โ€ฒ 8 =1 ๐‘“ โˆ’1 โ€ฒ (8)= 1 ๐‘“โ€ฒ 0 =1 ๐‘“โ€ฒ 0 ๐‘“ โˆ’1 โ€ฒ 8 =1

11 We have been more careful than usual in our statement of the differentiability result for inverse functions. You should notice that the differentiation formula for the inverse function involves division by fย '(fย -1(x)). We must therefore assume that this value is not equal to zero. There is also a graphical explanation for this necessity. Example. The graphs of the cubing function f(x) = x3 and its inverse (the cube root function) are shown below. Notice that fย '(x)=3x2 and so fย '(0)=0. The cubing function has a horizontal tangent line at the origin. Taking cube roots we find that fย -1(0)=0 and so fย '(fย -1(0))=0. The differentiation formula for fย -1 can not be applied to the inverse of the cubing function at 0 since we can not divide by zero. This failure shows up graphically in the fact that the graph of the cube root function has a vertical tangent line (slope undefined) at the origin.


Download ppt "8. DERIVATIVES OF INVERSE TRIG FUNCTIONS"

Similar presentations


Ads by Google